Cisplatin induces hippocampal neurotoxicity and cognitive impairment in rats through neuroinflammation, oxidative stress, and overexpression of glutamatergic receptors mRNA - Alhowail, Ahmad Hamad (Frontiers in Pharmacology, 2025)
Chemotherapy-induced cognitive deficits are a prevalent adverse effect in patients with cancer undergoing chemotherapy. We investigated cisplatin-induced neurotoxicity by assessing neuroinflammation and expression of glutamate receptors. Two groups of eight-week-old rats (n = 10 per group) were used: control and cisplatin-treated. Cisplatin (8 mg/kg, i. p.) was administered each 2 days for three cycles. From rats hippocampi, we measured: concentrations of nuclear factor-kappa B (NF-κB), tumor necrosis factor (TNF)-α, and interleukin (IL)-6); mRNA countenance of synapse-related proteins (α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) and N-methyl-D-aspartic acid receptors (NMDARs); levels of reactive oxygen species (ROS), nuclear factor erythroid 2-related factor 2 (Nrf-2), superoxide dismutase (SOD); mitochondrial complex I (MCI) activity; lipid peroxidation. The cisplatin group exhibited significant reductions in survival rate to 40% and body weight, confirming the initiation of cisplatin toxicity. In contrast with the control group, the cisplatin group exhibited notably increased hippocampal levels of pro-inflammatory substances (NF-κB, TNF-α, IL-6), synapse-related proteins (AMPARs, NMDARs), and oxidative-stress mediators (ROS, Nrf-2, SOD). Cisplatin treatment resulted in declined MCI activity and increased lipid peroxidation. These findings indicate that cisplatin-induced cognitive impairment may be mediated by heightened hippocampal neuroinflammation and overactivation of glutamatergic receptors.